2008
DOI: 10.1348/147608308x288762
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of treatment completers and non‐completers of an in‐patient treatment programme for male personality‐disordered offenders

Abstract: Findings suggest that teaching impulsive people a rational approach to social problem solving may reduce their level of non-completion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 16 publications
0
27
2
Order By: Relevance
“…However, the finding is inconsistent with that of a previous study reporting the reverse with poorer problem-solving skills being associated with program drop-out [39]. The present study did not obtain PCL-R scores which have been found to be an important marker of risk associated with drop-out [17].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the finding is inconsistent with that of a previous study reporting the reverse with poorer problem-solving skills being associated with program drop-out [39]. The present study did not obtain PCL-R scores which have been found to be an important marker of risk associated with drop-out [17].…”
Section: Discussioncontrasting
confidence: 99%
“…Third, other characteristics may have influenced out-come that were not investigated, in particular IQ [39] self-esteem [47], impulsivity [48,49] and psychopathy [17] have been associated with non-completion rates. Fourth, four of the five outcome measures were self-report and we aimed to minimize a positive bias by these being administered by researchers who had not been involved in treatment provision.…”
Section: Discussionmentioning
confidence: 99%
“…31 Engaging people with PD in treatment is a major challenge. 32,33 The social problem-solving approach enhances engagement by offering an accessible framework for change, supporting people in the experience of successful problem-solving and encouraging independence rather than reliance on therapy. Furthermore, the preliminary psychoeducation component of PEPS therapy aims to educate, build rapport and motivate people for problem-solving therapy.…”
Section: Social Problem-solving Therapymentioning
confidence: 99%
“…Post-discharge data were available for 81 patients who were classifi ed into three groups using criteria previously described by McMurran et al (2008); 1. Completers: Patients who were considered to have completed the treatment programme (n = 22).…”
Section: Outcome Groupsmentioning
confidence: 99%
“…Previous accounts of the service to be described have reported that, despite the use of standardised assessment methods to identify patients most likely to benefi t from treatment, approximately two thirds of patients admitted to the service fail to complete their treatment and that these non-completer patients can be classifi ed into two distinct groups of rule-breakers and those not engaged with treatment (McMurran et al, 2008).…”
Section: Introductionmentioning
confidence: 99%